Medical devices in India: a perspective of guidelines and the way forward - Sewlikar, Sandeep; Mahajan, Nilesh; Pillai, Reshmi; Desai, Anish (International Journal of Basic & Clinical Pharmacology, 2017)
In recent times, emerging countries including India have become favored destination for medical device companies to leverage the growth opportunities. However, the Indian regulatory system is not ready to meet the challenges that may come up with growing medical device business. It needs major amendments to current Drugs and Cosmetic Act 1940, to include medical device as a separate entity. Like in developed world, the challenges could be addressed by defining medical devices, risk based classification of devices, guidelines for device safety surveillance, and clinical trials for medical devices. Drugs and Cosmetic (Amendment) Bill 2013, which is yet to be released has addressed the concerns to some extent. However, it needs a major revamp to establish effective regulatory framework for medical devices.